A flexible high thermal conductivity composite phase change film and its preparation method and application
Through the composite film of paraffin, aramid nanofibers and carbon nanotubes, the problems of inaccurate temperature control of electronic equipment and low thermal conductivity of phase change materials are solved, and efficient and environmentally friendly lithium battery temperature regulation is achieved, which extends the Lithium battery life and reduces resource waste.
Patent Information
- Application Number
- CN202310366744.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-07
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2043-04-07
AI Technical Summary
The temperature control methods of existing electronic equipment have problems such as inaccurate temperature control, complex preparation process, and additional energy consumption. The thermal conductivity of phase change materials is low and easy to leak, so it is impossible to effectively regulate the temperature of lithium batteries.
Paraffin is used as the phase change matrix, aramid nanofibers are used as the three-dimensional framework, and carbon nanotubes are used as the thermal conductivity agent. A flexible high-thermal composite phase change film is prepared by vacuum impregnation method, combining the high phase change enthalpy of paraffin and the high thermal conductivity of carbon nanotubes. , improve the thermal conductivity and mechanical strength of the film to prevent leakage.
It has achieved a composite phase change film with high thermal conductivity, low leakage rate, good flexibility and high mechanical strength. It can be used directly as an electronic product shell, using the advantages of phase change to achieve temperature control, extend the life of lithium batteries, and reduce resource waste and environmental pollution.
Smart Images

Figure CN116285341B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of phase change materials, and in particular relates to a flexible high thermal conductivity composite phase change film and a preparation method and application thereof. Background Art
[0002] Mobile phones, computers and other electronic products generally generate heat during use, which causes lithium battery safety issues and accelerates lithium battery aging and retirement, resulting in resource waste and environmental pollution. Extending the service life of lithium batteries can reduce battery discards from the root. Current electronic equipment temperature control methods include heat sinks or heat sinks plus fans, etc., which have problems such as inaccurate temperature control, complex preparation processes, and extra energy consumption. They cannot fully meet the temperature control needs of electronic equipment and are not conducive to resource conservation.
[0003] Phase change materials can store or release a large amount of heat during the phase change process, and the phase change process is approximately isothermal. The high enthalpy change of phase change materials is expected to achieve effective regulation of battery temperature, but there are currently problems such as easy leakage of phase change materials and low thermal conductivity.
[0004] Therefore, being able to provide a composite phase change film with high thermal conductivity, mechanical strength, anti-leakage and other properties is an urgent problem to be solved by those skilled in the art. Summary of the invention
[0005] In view of this, the purpose of the present invention is to overcome the shortcomings of the prior art and provide a flexible phase change film that can significantly improve thermal conductivity, mechanical strength, leakage prevention and other properties, which can be directly used as the casing of electronic products such as mobile phones to ensure constant temperature operation of lithium batteries.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A flexible high-thermal-conductivity composite phase-change film, wherein the phase-change film uses paraffin as a phase-change matrix, aramid nanofibers as a three-dimensional skeleton, and carbon nanotubes as a thermal conductor.
[0008] The present invention adopts a vacuum impregnation method to fill paraffin as a phase change matrix into a porous aramid nanofiber film, and adds carbon nanotubes as a thermal conductor to prepare a paraffin / carbon nanotube / aramid nanofiber composite phase change film. The composite phase change film is not only small in size and light in weight, but also has a simple manufacturing process, reliable performance, economic and environmental protection, and has the characteristics of good flexibility, high phase change enthalpy, high thermal conductivity, high mechanical strength, low leakage rate, etc.
[0009] More importantly, the composite phase change film can be directly used as the outer shell of electronic products. It is flexible and convenient to use. It uses the advantages of its own phase change to achieve temperature control of electronic products without the consumption of external energy. It effectively realizes the concept of green energy saving and low carbon, ensures the constant temperature operation of lithium batteries, improves battery safety and service life, and alleviates the impact of battery disposal on resources and the environment. It is of great significance to building an energy-saving and environmentally friendly society.
[0010] Preferably, the aramid nanofiber is poly(p-phenylene terephthalamide) and / or poly(m-phenylene isophthalamide).
[0011] Compared with poly(o-phenylene phthalamide) and other heterocyclic aromatic polyamide fibers, poly(p-phenylene terephthalamide) and / or poly(m-phenylene isophthalamide) have excellent properties such as high strength, high temperature resistance, light weight, and stable chemical structure.
[0012] Preferably, the average diameter of the aramid nanofibers is 2-2000 nm.
[0013] The aramid nanofibers used in the present invention have a smaller average diameter and a larger specific surface area, which is conducive to the adsorption and filling of liquid paraffin and reduces the paraffin leakage rate.
[0014] Preferably, the carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
[0015] Carbon nanotubes have good mechanical properties, which can make composite materials show good strength, elasticity and fatigue resistance. At the same time, carbon nanotubes have high thermal conductivity. If a small amount of carbon nanotubes is doped into a composite material, the thermal conductivity of the composite material will be greatly improved.
[0016] Preferably, the content of the carbon nanotubes in the carbon nanotube / aramid nanofiber porous film is 0-3 wt %.
[0017] An appropriate amount of carbon nanotubes can simultaneously improve the mechanical properties, thermal conductivity, and phase change enthalpy of the phase change film, while an excessively high content causes carbon nanotube agglomeration, which is not conducive to improving the comprehensive performance of the phase change film.
[0018] Preferably, the melting point of the paraffin wax is in the range of 30-80°C.
[0019] Paraffin wax with this melting point range can ensure that the lithium battery is at a suitable operating temperature by absorbing or releasing heat.
[0020] According to the above-mentioned method for preparing a flexible high thermal conductivity composite phase change film, the method specifically comprises the following steps:
[0021] (1) mixing a carbon nanotube dispersion and an aramid nanofiber solution, and then successively subjecting the mixture to doctor blade coating and freeze drying to obtain a carbon nanotube / aramid nanofiber porous film;
[0022] (2) Filling the melted paraffin into the carbon nanotube / aramid nanofiber porous film to obtain a flexible and highly thermally conductive composite phase change film.
[0023] Preferably, the carbon nanotube dispersion in step (1) is a carbon nanotube / dimethyl sulfoxide dispersion, and the aramid nanofiber solution is an aramid nanofiber / potassium hydroxide / dimethyl sulfoxide solution.
[0024] Using dimethyl sulfoxide as a solvent can make the carbon nanotubes and aramid nanofibers have good dispersion and uniformity.
[0025] Preferably, the specific surface area of the carbon nanotube / aramid nanofiber porous film is 115-155 m 2 / g, pore size is 10-15nm.
[0026] The carbon nanotube / aramid nanofiber porous film has a large specific surface area, abundant pores, and pore sizes within the mesoporous range, which is conducive to the adsorption and filling of liquid paraffin and reduces the paraffin leakage rate.
[0027] Preferably, the filling in step (2) is performed by vacuum impregnation.
[0028] The porous film is filled with paraffin wax by vacuum impregnation method, the filling is relatively sufficient, the leakage of paraffin wax can be effectively prevented and the preparation process is simple.
[0029] Application of the flexible high thermal conductivity composite phase change film as described above or the flexible high thermal conductivity composite phase change film obtained by the preparation method as described above in the preparation of electronic devices.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] The present invention provides a flexible and highly thermally conductive composite phase change film and a preparation method thereof. The method has the advantages of simple preparation and low cost. The obtained composite phase change film has the characteristics of good flexibility, high phase change enthalpy, high thermal conductivity, high mechanical strength, low leakage rate, etc. The composite phase change film prepared by the present invention can be directly used as the outer shell of electronic products such as mobile phones, and utilizes its own phase change advantage to absorb or release heat, thereby meeting the temperature control requirements of the battery and significantly improving the safety and cycle life of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0033] Figure 1 This is the adsorption isotherm diagram of the carbon nanotube / aramid nanofiber porous film with different carbon nanotube mass fractions in Example 1.
[0034] Figure 2 This is the pore size distribution diagram of the carbon nanotube / aramid nanofiber porous film with different carbon nanotube mass fractions in Example 1.
[0035] Figure 3 These are SEM images of carbon nanotube / aramid nanofiber porous films with different carbon nanotube mass fractions in Example 1.
[0036] Figure 4 These are SEM images of paraffin / carbon nanotube / aramid nanofiber composite phase change films with different carbon nanotube mass fractions in Example 1.
[0037] Figure 5 The mechanical tensile stress-strain curves of the paraffin / carbon nanotube / aramid nanofiber composite phase change films with different carbon nanotube mass fractions in Example 1.
[0038] Figure 6 This is the leakage rate variation curve of the paraffin / carbon nanotube / aramid nanofiber composite phase change film with different carbon nanotube mass fractions in Example 1 over time (80°C).
[0039] Figure 7 This is the DSC test graph of the paraffin / carbon nanotube / aramid nanofiber composite phase change film with different carbon nanotube mass fractions in Example 1.
[0040] Figure 8 This is the temperature change curve of the lithium battery in Example 1 with the paraffin / carbon nanotube / aramid nanofiber composite phase change film as the outer shell (charging and discharging at an ambient temperature of 25°C). DETAILED DESCRIPTION
[0041] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] Example 1
[0043] A flexible high thermal conductivity composite phase change film, the preparation method comprises the following steps:
[0044] (1) Preparation of ANF-CNT porous films
[0045] 0.314, 0.631 and 1.933 mg of carbon nanotubes (CNTs) were respectively weighed and ultrasonically dispersed in dimethyl sulfoxide (DMSO), and stirred with a magnetic stirrer for 24 h to obtain a uniformly mixed CNT-DMSO dispersion solution;
[0046] Take 5 mL of aramid nanofiber (ANF)-dimethyl sulfoxide solution (containing 1 wt% KOH) with a concentration of 12.5 mg / mL, and slowly add the CNT-DMSO dispersion solution to the ANF-DMSO solution, stirring while adding to make it better dispersed, and use a magnetic stirrer to stir for 24 hours to obtain a uniformly mixed ANF-CNT-DMSO solution;
[0047] Then, a 1000 μm scraper was used to coat the glass slide to prepare an ANF-CNT gel film, which was then completely immersed in water to displace DMSO with water and remove KOH at the same time. After 1 hour of displacement, the film and the glass slide were separated, the glass slide was taken out, and the film was placed in water to continue displacement for 12 hours to obtain a porous ANF-CNT film.
[0048] A 50 vol% tert-butyl alcohol (TBA) solution was prepared, and the ANF-CNT porous film replaced in water was placed in the prepared TBA solution for replacement for 12 h. The replaced film was first frozen in a vacuum freezer for 2 h, and then vacuum-dried for 48 h, thereby preparing ANF-CNT porous films with CNT contents of 0, 0.5, 1.0 and 3.0 wt%, which were marked as ANF, ANF-CNT0.5, ANF-CNT1 and ANF-CNT3 (thickness range of 900-1100 μm), respectively;
[0049] (2) Preparation of PW / ANF-CNT composite phase change films
[0050] Take 250g paraffin wax (PW, melting point 56°C) and place it in a beaker, heat it in a water bath to melt, and set aside;
[0051] The ANF-CNT porous film obtained in step (1) is added to the PW melt to allow the PW to fully immerse in the pores of the ANF-CNT film, and then placed in a vacuum drying oven in a vacuum state until it cools to room temperature; the above steps are repeated multiple times until the pores of the ANF-CNT composite film are completely filled with PW; the above composite film is clamped with a glass plate and continued to dry in a vacuum for 24 hours to obtain a PW / ANF-CNT composite phase change film, and the composite phase change films with CNT contents of 0, 0.5, 1.0 and 3.0 wt% are marked as PW / ANF-CNT0, PW / ANF-CNT0.5, PW / ANF-CNT1 and PW / ANF-CNT3, respectively (the content of PW in the phase change film is 70-80 wt%);
[0052] in, Figure 1 The adsorption isotherms of carbon nanotube / aramid nanofiber porous films with different carbon nanotube mass fractions are obtained using the BET specific surface area detection method. It can be seen from the figure that the four groups of porous films all have the characteristics of four types of adsorption isotherms. At the beginning, the adsorption line is relatively flat. In the high relative pressure area, capillary condensation occurs and the adsorption line rises rapidly, indicating that the pores are mainly mesopores.
[0053] Figure 2 The pore size distribution diagram of carbon nanotube / aramid nanofiber porous films with different carbon nanotube mass fractions was obtained by testing with a pore size analyzer. It can be seen from the figure that the average pore size of the four groups of porous films are all within the mesoporous range of 2-50nm, and there are many micropores and a small amount of macropores, with mesopores being the main ones.
[0054] Figure 3 These are SEM images of carbon nanotube / aramid nanofiber porous films with different carbon nanotube mass fractions, obtained using scanning electron microscopy. Among them, a is ANF, b is ANF-CNT0.5, c is ANF-CNT1, and d is ANF-CNT3. It can be seen from the figure that before filling with paraffin, the porous film has abundant pores.
[0055] Figure 4 The SEM images of paraffin / carbon nanotube / aramid nanofiber composite phase change films with different carbon nanotube mass fractions were obtained using a scanning electron microscope. Among them, a is PW / ANF, b is PW / ANF-CNT0.5, c is PW / ANF-CNT1, and d is PW / ANF-CNT3. It can be seen from the figure that after filling with paraffin, the film has almost no gaps. By comparison, it can be seen that the paraffin filling is relatively sufficient.
[0056] Figure 5 The mechanical tensile stress-strain curve of paraffin / carbon nanotube / aramid nanofiber composite phase change film with different carbon nanotube mass fractions was obtained by testing with a universal testing machine. It can be seen from the figure that the film has a large plastic deformation, high mechanical tensile strength and good toughness.
[0057] Figure 6 The leakage rate of paraffin / carbon nanotube / aramid nanofiber composite phase change film with different carbon nanotube mass fractions varies with time (80℃). Four groups of samples were placed in an 80℃ drying oven, and the mass was measured every 30 minutes for 8 hours. It can be seen from the figure that the paraffin leakage rate is reduced by 65-75%, indicating that filling PW in the porous film by vacuum impregnation method can effectively prevent paraffin leakage.
[0058] Figure 7The DSC test diagram of paraffin / carbon nanotube / aramid nanofiber composite phase change film with different carbon nanotube mass fractions was obtained by differential scanning calorimetry. It can be seen from the figure that pure paraffin begins to melt at 25°C, reaches a peak value at 57.5°C, and completely melts at 63°C. After paraffin is filled into the porous film, the melting peak shifts slightly to the right, and after doping with carbon nanotubes, the thermal conductivity is enhanced, and the melting peak begins to shift to the left. The film has a large phase change enthalpy, reaching 183-193 J / g, indicating that the phase change film has a good heat storage effect.
[0059] Figure 8 The surface temperature change curve of a lithium battery with a paraffin / carbon nanotube / aramid nanofiber composite phase change film as its shell (charging and discharging at an ambient temperature of 25°C) was obtained by testing with a multi-channel temperature tester. It can be seen from the figure that a lithium battery will generate a lot of heat during the charging and discharging stages, causing the battery surface temperature to rise rapidly. After a layer of phase change film is attached to the battery surface, the battery surface temperature drops significantly.
[0060] Comparative Example 1:
[0061] A composite phase change film and preparation method thereof, CN202111352623.1.
[0062] The composition of the composite phase change film described in this patent includes 5-13% reinforcing resin, 8-12% oil-absorbing resin, 40-80% straight-chain alkanes, 20-35% thermal conductive fillers, 1-3% lubricants, 3-5% binders, 0.5-1% stabilizers, 1-2% coupling agents, and 0.1-0.5% pigments; and the preparation of the composite phase change film includes multiple complex processes such as rubber mixing, granulation, extrusion, calendering, curing and edge sealing. The heat storage capacity of the composite phase change film is 100-180J / g.
[0063] Compared with the above patents, this patent uses different and fewer raw materials, which are rich in sources, easy to obtain at a low price, and environmentally friendly. In addition, the preparation process of the phase change film is simple, the production equipment investment is low, and no waste gas or waste liquid is generated. In addition, the phase change enthalpy of the film prepared by this patent is higher than that of the phase change film prepared by the above patents.
[0064] Comparative Example 2:
[0065] A phase change thin film temperature control material, CN202110390789.6.
[0066] The phase change film temperature control material described in the patent contains a three-layer structure, the middle layer is a phase change microcapsule film, and the upper and lower layers are high thermal conductivity graphite films. The preparation process of the phase change temperature control material is: the high thermal conductivity graphite film is used as the substrate, the phase change microcapsule film is laid on it, and then covered with a layer of high thermal conductivity graphite film, and then transferred to the tablet press, and rolled by a double roller machine to press into a uniform phase change film temperature control material, and finally removed through the demolding frame.
[0067] Compared with this patent, this patent uses different types of raw materials with abundant sources, and the preparation process of the phase change film is simple. The film has a single-layer structure and a higher phase change enthalpy, reaching 183-193 J / g.
[0068] The various embodiments are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to in detail.
[0069] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A flexible high thermal conductivity composite phase change film, characterized in that: The phase change film uses paraffin as a phase change matrix, aramid nanofibers as a three-dimensional skeleton, and carbon nanotubes as a thermal conductor; the content of the carbon nanotubes in the carbon nanotube / aramid nanofiber porous film is 0.5-3wt%; The method for preparing the composite phase change film specifically comprises the following steps: (1) A carbon nanotube dispersion and an aramid nanofiber solution are mixed and then successively subjected to doctor blade coating and freeze drying to obtain a carbon nanotube / aramid nanofiber porous film; the carbon nanotube dispersion is a carbon nanotube / dimethyl sulfoxide dispersion, and the aramid nanofiber solution is an aramid nanofiber / potassium hydroxide / dimethyl sulfoxide solution; the specific surface area of the carbon nanotube / aramid nanofiber porous film is 115-155 m 2 / g, pore size is 10-15nm; (2) filling the carbon nanotube / aramid nanofiber porous film with melted paraffin to obtain a flexible and highly thermally conductive composite phase change film; The flexible high thermal conductivity composite phase change film is used in preparing electronic equipment casings.
2. A flexible high thermal conductivity composite phase change film according to claim 1, characterized in that: The aramid nanofiber is poly(p-phenylene terephthalamide) and / or poly(m-phenylene isophthalamide).
3. The flexible high thermal conductivity composite phase change film according to claim 1, characterized in that: The average diameter of the aramid nanofiber is 2-2000nm.
4. The flexible high thermal conductivity composite phase change film according to claim 1, characterized in that: The carbon nanotubes are single-walled carbon nanotubes and / or multi-walled carbon nanotubes.
5. The flexible high thermal conductivity composite phase change film according to claim 1, characterized in that: The melting point of the paraffin wax ranges from 30 to 80°C.
6. The flexible high thermal conductivity composite phase change film according to claim 1, characterized in that: The filling in step (2) is performed by vacuum impregnation.
Citation Information
Patent Citations
Paraffinic based carbon nano-tube compound phase transformation heat accumulating material and preparation thereof
CN101407714A
Aerogel-based host-guest composite film and preparation method and application thereof
CN113527761A